Family Problems Experienced by Students of the University of Jordan - Hatahet, Faten Saad; Hamed Alqudah, Mohammed Amin (European Scientific Journal, ESJ, 2016)
The study has aimed at identifying the family problems among the students of the University of Jordan. The descriptive survey method has been used, and the questionnaire has been used as a tool for the study. (604) students have been selected in a stratified random manner from the University of Jordan as a sample for the study. The study results have showed that the most important and prominent family problems experienced by the University of Jordan students are: Problems in communication between family members, problems with emotional expression, lack of respect among family members, and lack of trust in the relationship with the parents. The results also showed that there are no statistically significant differences in family problems experienced by the University of Jordan students from the viewpoint of the students themselves due to the variables of gender, college, and the interaction between them both.